Managing Quality of The Carton Box Production Process CV GGG Using New Seven Tools Method - Ari Aprian Amartya; Nina Aini Mahbubah (Fakultas Teknik, 2022)
Quality control is an activity to certify that the process meets the enterprise's standards. The Quality Division of CV GGG has been encouraged to find suitable methods to decrease current larger than common defects. This research aims to evaluate the quality of the carton box production line based on the new seven tools approach. This approach begins with affinity diagrams followed by interrelationship diagrams, tree diagrams, matrix analysis diagrams, activity network diagrams, and process decision program charts. The study identified two defects: untidy paint quality and fragmented fractions throughout the production line. Furthermore, implementing the new seven tools has been distinguished primary factors causing defects. The first factor is the unavailability of manual Standard Operational procedures for maintenance schedules. The next factor is unnecessary movement during storage and transfer of materials and improper working environment on the production workshops. Several scenarios have been proposed to eliminate such defects and increase productivity.